Pengaruh Lingkungan Belajar, Disiplin Belajar, Motivasi Belajar terhadap Hasil Belajar pada Tahfiz di SMKN 1 Sungai Aur (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2026)
This study aims to examine the impact of the learning environment, perseverance in learning, and learning motivation on the Tahfiz achievement of students at SMKN 1 Sungai Aur. The research method used is quantitative with a causal associative design. The population studied includes all students from grades X, XI, and XII at SMKN 1 Sungai Aur, using proportional random sampling techniques. Data were collected through the use of closed questionnaires for the variables of learning environment, perseverance in learning, and learning motivation, as well as documentation of Tahfiz scores as indicators of learning achievement. Data analysis includes validity testing, reliability testing, classical assumption testing, and multiple linear regression analysis. The findings indicate that the learning environment, perseverance in learning, and learning motivation together have a significant influence on Tahfiz learning achievement. Individually, all three independent variables also have a significant impact, with learning motivation being the most influential variable. This study emphasizes the importance of creating a supportive learning environment, cultivating perseverance in learning, and strengthening spiritual motivation to improve the quality of Tahfiz learning.